Post-vaccination Severity and Outcome of COVID-19 - Nimra Kanwal; Nauman Ismat Butt; Samrina Sadaf; Syed Asif Hussain; Anum Rasheed; Sadia Babu (Journal of University Medical & Dental College, 2023)
BACKGROUND & OBJECTIVE: COVID-19 infection can occur even after vaccination but vaccination aids to reduce risk of severe COVID-19, hospitalization and mortality. Objective of present study was to determine severity and outcome of COVID-19 infection developed post-vaccination.METHODOLOGY: This observational cross-sectional study was conducted at Agha Khan Medical Center Gilgit Pakistan from July 2021 to July 2022. COVID-19 infection was diagnosed by a positive COVID-19 PCR. After taking informed consent, 80 fully vaccinated patients of new onset COVID-19 aged 20-100 years of both genders were enrolled. Demographic information was noted and severity of COVID-19 infection assessed. All patients were followed up to 4 weeks of symptom onset, recovery or death whichever occurred earlier.RESULTS: Mean age was 49.5+19.5 years with 47 (58.7%) males. Seven (8.8%) patients were smokers, 14 (17.5%) hypertensive, 07 (8.8%) diabetic, 05 (6.3%) had ischemic heart disease and 04 (5.0%) had asthma. Forty-eight (60.0%) patients had received Sinopharm vaccine, 21 (26.3%) Sinovac, 08 (10.0%) Cansino, 02 (2.5%) Astrazeneca and 01 (1.3%) Moderna. Fifty-six (70.0%) had mild COVID-19 disease, 07 (8.8%) had moderate disease, 10 (12.5%) had severe disease while 07 (8.8%) had critical disease. Twenty-four (30.0%) patients were admitted with mean hospital stay 4.7+7.4 days. Sadly, 08 (10.0%) patients passed away. Disease severity showed significant association with age p-value=0.014 and co-morbid conditions with p-value=0.013.CONCLUSION: Post-vaccination COVID-19 illness was mild in more than two-thirds patients. Male sex, advanced age and presence of co-morbid diseases were associated with severe disease and mortality.